Efficacy of nebulized colistin-based therapy without concurrent intravenous colistin for ventilator-associated pneumonia caused by carbapenem-resistant Acinetobacter baumannii - Kim, Yong Kyun; Lee, Jae Ha; Lee, Hyun-Kyung; Chung, Byung Cheol; Yu, Seung Jung; Lee, Ho-Young; Park, Jin-Han; Kim, Sunyoung; Kim, Hyeon-Kuk; Kiem, Sungmin; Jang, Hang-Jea (Journal of Thoracic Disease; Vol 9, No 3 (March 28, 2017): Journal of Thoracic Disease, 2017)
Background: Although there have been studies regarding the role of nebulized colistin as adjunctive therapy of ventilator-associated pneumonia (VAP) caused by carbapenem-resistant Acinetobacter baumannii (CRAB), a paucity of information on the efficacy of nebulized colistin as monotherapy is available. Methods: We retrospectively reviewed 219 patients with VAP caused by CRAB treated with either intravenous (n=93) or nebulized colistin (n=126), from March 2010 to November 2015. Factors related to clinical failure was assessed using propensity-score-matched analysis. Results: Of 219 patients, 39 patients from each group (n=78) were matched after covariate adjustment using propensity score. There were no significant differences in baseline characteristics as well as the rates of clinical failure between the propensity-score-matched groups [Odds ratio (OR), 0.48; 95% confidence interval (CI), 0.19–1.19; P=0.11], while a significantly lower rate of acute kidney injury (AKI) during colistin therapy (18% vs. 49%, P=0.004) was observed in nebulized colistin group. In addition, multivariable analysis revealed that nebulized colistin did not significantly alter the rate of clinical failure [adjusted odds ratio (aOR), 0.36; 95% CI, 0.12–1.09; P=0.070]. Instead, medical intensive care unit (ICU) admission (aOR, 7.14; 95% CI, 1.60–32.00; P=0.010), and septic shock (aOR, 3.93; 95% CI, 1.27–12.17; P=0.018) were independent risk factors for clinical failure. Conclusions: Our findings suggest that nebulized colistin-based therapy, even without concurrent administration of intravenous colistin, may be an effective and safe treatment option for VAP caused by CRAB.